The Translation of D. H. Lawrence’s Metaphors: the French Censored Passages in “The Rainbow” as a Case in Point - Louzir, Aïcha (Respectus Philologicus, 2018)
[full article and abstract in English]The aim of this study is to explore D. H. Lawrence’s style through the prism of his use of metaphor. As a particularly enlightening method, I shall compare some of the censored passages in “The Rainbow” (1915) against their French translations (1939, 2002). Focusing my attention on their stylistic particularities, I will examine the manner in which they were translated into French. The central argument of my paper is that Lawrence’s metaphors related to the body are a relevant tool highlighting the author’s vision of human relationships, within the context of prevalent views in the beginning of the 20th century. The British authorities banned “The Rainbow” since its first publication and accused Lawrence of pornography. Therefore, it is important to glance back in order to understand the reason behind the censorship and see that the translations of Lawrence’s oeuvre were decisive in spreading his ideas beyond the frontiers of his country of origin. My analysis mainly draws on a descriptive approach but it is at the crossroads of several paradigms, namely the interpretative approach in Translation Studies and the cognitive approach to the study of metaphors.
Keywords: Style, Metaphor, Mental Representation, Translation, Body